On the issue of private expenses on health care - Omirbayeva, B.S. (BUKETOV BUSINESS REVIEW, 2019)
The development of health care systems around the world is always an urgent task, which is aimed at improving the health of the population. However, any improvement is always associated with high costs. That is why monitoring health expenditure is an important element in decision-making. One of the objects of attention is the high private expenses observed in Kazakhstan, which threaten the availability of health care services, increase inequalities in the level of health services and place an additional burden on the poorest segments of society, associated with the need to purchase expensive treatment with the ensuing consequences for economic growth. The significant limitation of free medical care or the lack of public funding leads to an increase in the share of private expenditure as a result of the population's forced acquisition of the necessary assistance at the expense of personal funds. On another hand, with an increase in public funding, the amount of personal expenses of the population may increase due to related expenses that are not covered by public health (for example, the purchase of medicines), which may explain the situation with regard to the high level of private costs in the health care of the Republic of Kazakhstan.